Analisis Kualitas Informasi Akuntansi Dan Risiko Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (Sakti) Terhadap Efektivitas Pengelolaan Keuangan Di Direktorat Pembinaan Masyarakat Polda Jatim - Intan Pandini; Mulyanto Nugroho; Mochammad Arifin (Jurnal Ekonomi Manajemen dan Bisnis, 2025)
The Directorate of Community Development of the East Java Regional Police is a work unit with an annual budget allocation of around Rp10 billion. The effectiveness of financial management is important to support various community development programs. This study aims to analyze the implementation of the Agency-Level Financial Application System or called SAKTI at the Directorate of Community Development of the East Java Regional Police. The focus of the study includes the quality of accounting information generated by the application, implementation risks analyzed using SAS Number 94, and the effect of the application on the effectiveness of financial management. The results showed that SAKTI improved the quality of accounting information through indicators of understandability, timeliness, reliability, and relevance. However, risks were found such as dependence on technology, limited application features, and personnel shortages. This study recommends strengthening user training and internal controls to mitigate these risks. These findings contribute to optimizing the use of SAKTI to support transparent and accountable financial governance in government agencies.